Cross-cultural neuropsychological assessment in Europe: Position statement of the European Consortium on Cross-Cultural Neuropsychology (ECCroN). Issue 3 (14th March 2022) - Franzen, Sanne; ,; Watermeyer, Tam J.; Pomati, Simone; Papma, Janne M.; Nielsen, T. Rune; Narme, Pauline; Mukadam, Naaheed; Lozano-Ruiz, Álvaro; Ibanez-Casas, Inmaculada; Goudsmit, Miriam; Fasfous, Ahmed; et al.
Abstract: Objective: : Over the past decades European societies have become increasingly diverse. This diversity in culture, education, and language significantly impacts neuropsychological assessment. Although several initiatives are under way to overcome these barriers – e.g. newly developed and validated test batteries – there is a need for more collaboration in the development and implementation of neuropsychological tests, such as in the domains of social cognition and language. Method: : To address these gaps in cross-cultural neuropsychological assessment in Europe, the European Consortium on Cross-Cultural Neuropsychology (ECCroN) was established in 2019. Results: : ECCroN recommends taking a broad range of variables into account, such as linguistic factors, literacy, education, migration history, acculturation and other cultural factors. We advocate against race-based norms as a solution to the challenging interpretation of group differences on neuropsychological tests, and instead support the development, validation, and standardization of more widely applicable/cross-culturally applicable tests that take into account interindividual variability. Last, ECCroN advocates for an improvement in the clinical training of neuropsychologists in culturally sensitive neuropsychological assessment, and the development and implementation of guidelines for interpreter-mediated neuropsychological assessment in diverse populations in Europe. Conclusions: : ECCroN may impact research and clinical practice by contributing to existing theoretical frameworks and by improving the assessment of diverse individuals across Europe through collaborations on test development, collection of normative data, cross-cultural clinical training, and interpreter-mediated assessment.